The Molecular Basis of Human Cancer - Coleman, William B.; Tsongalis, Gregory J. (Springer New York : Imprint: Humana Press, 2017)
This book covers the concepts of molecular medicine and personalized medicine. Subsequent chapters cover the topics of genomics, transcriptomics, epigenomics, and proteomics, as the tools of molecular pathology and foundations of molecular medicine. These chapters are followed by a series of chapters that provide overviews of molecular medicine as applied broadly to neoplastic, genetic, and infectious diseases, as well as a chapter on molecular diagnostics. The volume concludes with a chapter that delves into the promise of molecular medicine in the personalized treatment of patients with complex diseases, along with a discussion of the challenges and obstacles to personalized patient care. The Molecular Basis of Human Cancer, Second Edition, is a valuable resource for oncologists, researchers, and all medical professionals who work with cancer.- Resumé vydavatel
Keywords: maligní nádorová onemocnění; molekulární biologie; molekulární medicína; cancer; molecular biology; molecular medicine; elektronické knihy; sborníky; electronic books; papers of several authors